Caracterização molecular e imunológica do veneno de Tityus fasciolatus e sua ação sobre camundongos - Priscylla Tatiana Chalfun Guimaraes (2009)
The aim of the study was to investigate the specie Tityus fasciolatus scorpion found in the Central of Brazil. This study was performed through molecular characterization, lethal dose and biochemical, anatomo-histopathological and immunological alterations in mice. Sixty Swiss CF1 mice, male, (18-20kg) were used to determine lethality assays T. fasciolatus (LD50) by subcutaneous injection (SC). The anatomo-histopathological examination was performed with the animals who died during the lethality assays (LD50). To study the blood profile and biochemistry fifty Swiss CF1 mice, male, 30g were used divided into three groups (G) (n= 18) SC with: 50l of PBS (G1), 24g of venom of T. fasciolatus (G2) and 8g venom of T. serrulatus (G3). Each group was subdivided into three subgroups (n = 6) according to the time of blood sample was taken at 1h , 8h and 24h after inoculation of the venom. It was investigated blood profile and levels of cortisol, urea, creatinine, creatine kinase, MB isoenzyme, aminotransferase aspartate, lactate dehydrogenase, amylase, glucose, total protein and fractionated. The molecular characterization was evaluated by molecular extraction and purification of RNA and RT-PCR technique with primers from the sequencie of toxin from venom of T. serrulatus. The antigenic cross-reaction between the toxins of venoms and neutralization ability the anti-T. serrulatus against that of the T. fasciolatus was determined by using the Western Blotting technique. The protein concentration was determined by SDS-PAGE. The LD50 of the venom of T. fasciolatus for mice was 59.65mg. Histopathological changes were observed in heart, lung and brain of mice who died. The venom of T. fasciolatus at a dose of 24g caused piloerection, nocioceptive behavior, nasal and oral sharp, dyspnoea, itching on the face and reflexes exacerbated, polycythemia, leukocytosis with lymphocytosis. The venom of T. fasciolatus showed similarity with the venom of T. serrulatus, reactivity and cross-neutralization. The methodology with primers from the venom of T. serrulatus and RT-PCR was effective for the isolation and obtain clones containing sequences corresponding to the mRNA transcripts from the venom gland of T. fasciolatus such as Tf1, Tf3 and Tf4a. In the neutralization assays the antivenon anti-T. serrulatus was able to effectively neutralize the venom of T. fasciolatus